Are PECTIN ESTERASE INHIBITOR Genes Involved in Mediating Resistance to Rhynchosporium commune in Barley? - Marzin, Stephan; Hanemann, Anja; Sharma, Shailendra; Hensel, Götz; Kumlehn, Jochen; Schweizer, Günther; Röder, Marion S. (PLOS ONE, 2016)
A family of putative PECTIN ESTERASE INHIBITOR (PEI) genes, which were detected in the genomic region co-segregating with the resistance gene Rrs2 against scald caused by Rhynchosporium commune in barley, were characterized and tested for their possible involvement in mediating resistance to the pathogen by complementation and overexpression analysis. The sequences of the respective genes were derived from two BAC contigs originating from the susceptible cultivar ‘Morex’. For the genes HvPEI2, HvPEI3, HvPEI4 and HvPEI6, specific haplotypes for 18 resistant and 23 susceptible cultivars were detected after PCR-amplification and haplotype-specific CAPS-markers were developed. None of the tested candidate genes HvPEI2, HvPEI3 and HvPEI4 alone conferred a high resistance level in transgenic over-expression plants, though an improvement of the resistance level was observed especially with OE-lines for gene HvPEI4. These results do not confirm but also do not exclude an involvement of the PEI gene family in the response to the pathogen. A candidate for the resistance gene Rrs2 could not be identified yet. It is possible that Rrs2 is a PEI gene or another type of gene which has not been detected in the susceptible cultivar ‘Morex’ or the full resistance reaction requires the presence of several PEI genes.